Kesalahan Siswa dalam Menyelesaikan Soal Cerita Sistem Persamaan Linear Tiga Variabel Berdasarkan Prosedur Polya - Handayani, Ucik Fitri; Aisyah, Siti (JURNAL PENELITIAN PENDIDIKAN MATEMATIKA DAN SAINS, 2024)
The objective of this study is to describe students' errors in solving word problems related to the Three-Variable Linear Equation System based on Polya's procedure. The errors identified correspond to various stages of Polya's problem-solving method. This research adopts a descriptive approach with qualitative methods. Data collection involved tests and interviews, with the subjects being 10th-grade students at MA Miftahul Ulum Gondanglegi, East Java, Indonesia. The data analysis technique employed data reduction, presentation, and conclusion drawing. The research findings revealed that there are four main types of errors made by students. The most frequent error, accounting for 42%, was in rechecking the solutions obtained, indicating a tendency among students to be less thorough in reviewing their answers. Conversely, the least frequent error, occurring at 8%, was in understanding the problems, suggesting that students generally have a good grasp of what is known and what is asked in the problem. Several factors contribute to these errors, including students' lack of caution in reading and understanding the problems, inaccuracies in performing calculations, a lack of habit in writing down solutions in a sequential and systematic manner, and insufficient practice in verifying their answers.